PKM Kelompok Usaha Terasi Desa Bonang Kecamatan Lasem dalam Upaya Menghadapi Permasalahan Cuaca - Rikah Rikah; Agustina Widodo (Journal of Dedicators Community, 2019)
The aim of the Community Partnership Program (PKM) is to increase community income through increased quality and quantity of shrimp paste production. This Partnership Program is business group of shrimp paste (rebon) in Bonang Village, Lasem Subdistrict, Rembang Regency with partners of shrimp paste craftsmen. The method carried out in the Community Partnership Program (PKM) is accompaniment to the group in understanding about the drying machine and get the information of capital provider. The realization of a drying machine that aims to ensure the continuity of the production process without having dependency by weather conditions and limited drying area. By using a shrimp paste drying machine, the group of shrimp paste craftsmen can still produce even in rainy and cloudy weather condition. The group of craftsmen can make product diversification, which is making ready-made cooked shrimp paste and be more hygienic by using shrimp paste drying machine.